Efektivitas Kebijakan Pajak Penjualan atas Barang Mewah (PPnBM) terhadap Perilaku Konsumsi Konglomerat di Indonesia - Juanita Wahyu Pramudipta; Fadjar Harimurti; Aris Eddy; Sinta Putriana (Indo Publishing, 2026)
The Luxury Goods Sales Tax (PPnBM) policy is designed not only as a state revenue instrument but also as a regulative tool (fungsi regulerend) to foster social justice and curb the regressive consumption patterns of high-net-worth individuals. However, regulatory loopholes are frequently exploited by conglomerates to minimize this tax burden. This study aims to evaluate the effectiveness of PPnBM collection on ultra-luxury goods such as supercars, private jets, and other luxury asset ownership instruments and to analyze the accompanying tax avoidance patterns. Utilizing a descriptive qualitative method with a policy analysis and literature review approach, this study finds that the imposition of high PPnBM is often countered by tax burden shifting schemes, such as purchasing assets through legal entities (corporations) to be claimed as deductible fiscal expenses. This study recommends the imperative strengthening of the substance over form regulation to optimize tax equity